What are princes made of? (Elite burials in the Early iron Age) - Potrebica, Hrvoje (Array, 2004)
Our perception of the Early Iron Age social structure is largely a result of the information derived from the burial assemblages. Elite burials form the most important class in such an approach, especially when they take form of the so-called princely graves. The burials of distinctive individuals are clearly marked by their monumental nature and/or abundance of exquisite grave goods ; however, it is not easy to determine objective and universal criteria for a definition of princely graves. It gets even more complicated when it comes to the definition of the elite, which appears to be a rather vague term in general. The concept of the elite is closely related to the social structure of a certain community and rooted in its material and spiritual culture. The Early Iron Age burials in the Hallstatt area and neighbouring regions provide a good case study for further conceptual analysis. It explains the distinction between the elite and "ordinary" burials and their symbolic representation, or how certain communities define the elite and mark it in their burial rituals. It seems that definition patterns were determined by features of the social structure of particular community. Common denominators of that process are concepts of continuity and distribution. The elite consisted of individuals who were important for the structural continuity of the community, on both mythological and social level. The members of the elite are those individuals whose destiny functions as pars pro toto for the whole group. The power of the elite lies in control of external and internal distribution of goods and ideas. They are recognized as the only force capable of mobilizing the collective resources of their community in order to achieve any predetermined goal.